Turning the flywheel: mobilizing the JBI model of evidence-based healthcare. Issue 1 (14th March 2023) - Jordan, Zoe; Pilla, Bianca; Porritt, Kylie; Munn, Zachary; Aromataris, Edoardo; Lockwood, Craig
Abstract : ABSTRACT: Since its emergence in the 1990s, evidence-based healthcare (EBHC) has made great strides in locating, synthesizing, summarizing, and disseminating evidence, but sustainable mechanisms for getting trustworthy evidence into policy and practice continues to be less well understood. We propose that there is an EBHC 'Flywheel' that begins and ends with culture and the development of adaptive but disciplined approaches that generate new 'norms' in relation to EBHC. In mechanics, a flywheel is a device that uses momentum to create rotational energy. The concept of a 'flywheel effect' has been adopted in management fields to demonstrate how change in organizations or practices rarely happen in one fell swoop; rather, sustainable change requires energy and persistent effort. This energy might be exemplified by leadership to get the wheel moving, but it needs to be guided, channelled, harnessed and supported throughout the rest of the organization. To achieve sustainable momentum, it is necessary to communicate with transparency the EBHC principles, practices, and perspectives that are considered of broad organizational value to generate cohesion and understanding about practice expectations. With a common vision, cooperation and collective identity in place, true multidisciplinary collaboration underpinned by EBHC is possible. The final component in the EBHC flywheel, capacity, is self-generating (i.e. you do not need 'more time' or 'more resource' for EBHC as EBHC is embedded in the fabric and fibre of the organization). This shifts the notion of EBHC initiatives from being 'in addition to' or being singular one-off initiatives or projects to being part of the lifeblood of how the organization functions. EBHC is, ultimately, a human-to-human endeavour. It relates to individuals connecting and committing to a common purpose. The 'four C's' that underpin the JBI Model (culture, communication, collaboration, and capacity) are the organizational navigational instruments and roadmaps required to provide the human focus/lens that is needed.